Morphological and Wear behaviour of new Al-SiCmicro-SiCnano hybrid nanocomposites fabricated through powder metallurgy. (27th April 2018) - Arif, Sajjad; Alam, Md Tanwir; Aziz, Tariq; Ansari, Akhter H
Abstract: In the present work, aluminium matrix composites reinforced with 10 wt% SiC micro particles along with x% SiC nano particles (x = 0, 1, 3, 5 and 7 wt%) were fabricated through powder metallurgy. The fabricated hybrid composites were characterized by x-ray diffractometer (XRD), scanning electron microscope (SEM), energy dispersive spectrum (EDS) and elemental mapping. The relative density, hardness and wear behaviour of all hybrid nanocomposites were studied. The influence of various control factors like SiC reinforcement, sliding distance (300, 600, 900 and 1200 m) and applied load (20, 30 and 40 N) were explored using pin-on-disc wear apparatus. The uniform distribution of micro and nano SiC particles in aluminium matrix is confirmed by elemental maps. The hardness and wear test results showed that properties of the hybrid composite containing 5 wt% nano SiC was better than other hybrid composites. Additionally, the wear loss of all hybrid nanocomposites increases with increasing sliding distance and applied load. The identification of wear phenomenon were studied through the SEM images of worn surface.